Gravimetric and volumetric capacitive performance of polyindole/carbon black/MoS2 hybrid electrode material for supercapacitor applications - Majumder M.; Choudhary R.B.; Koiry S.P.; Thakur A.K.; Kumar U. (My University, 2025)
We report the facile in situ chemical oxidative synthesis and detailed electrochemical evaluation of polyindole (PIn) and its composites with carbon black (CB) and molybdenum disulfide (MoS2) for application in supercapacitor as an electrode material. PIn, owing to its unique property of possessing a fused benzene and a pyrrole ring, proves to be a very interesting material. Material design involves incorporation of conducting CB and sheet like MoS2 into the PIn matrix in order to promote charge transportation. This results into the PIn/CB/MoS2 ternary composite with improved electrochemical performance. PIn/CB/MoS2-2 exhibits a gravimetric capacitance of 442 F g−1 and a volumetric capacitance of 512.7 F cm−3 at the current density of 1 A g−1. Additionally, it exhibits a high coulombic efficiency of 96.7% at the current density of 10 A g−1 together with a long term cyclic life (92.3% capacitance retention after 5000 cycles at 10 A g−1). Hence, PIn/CB/MoS2-2 composite proves to be very effective with fairly improved gravimetric and volumetric performances as an electrode material for supercapacitor applications. © 2017 Elsevier Ltd